An insight into magma supply to the Karoo Igneous Province a geochemical investigation of Karoo dykes adjacent to the Northwestern sector of the Lesotho volcanic remnant - Mitha, Vindina Ramesh (Rhodes University, Faculty of Science, Department of Geology, 2006)
The emplacement of continental flood basalt provinces is often ascribed to fissure eruption. However, in many provinces the locations of actual vent complexes remains illusive. In southern Africa, the Karoo continental flood basalt province was erupted during the Jurassic between 183 and 179 Ma. The southernmost outcrop of the Karoo continental flood basalt lavas is the Lesotho remnant; and is comprised of the Drakensberg Group which forms the uppermost portion of the Karoo Supergroup. The geochemical stratigraphy for the Drakensberg Group is well established. At the base, there are a number of small volume compositionally diverse units, which form the Barkly East Formation, overlying which, there are larger volume, compositionally less variable units of the Lesotho Formation, which form the bulk of the volcanic sequence. The Lesotho remnant is associated with an abundance of dykes in the adjacent vicinity. This suggests that the lavas were fed from local rather than distal eruption sites. This study presents whole rock major and trace element data for 94 dykes and three sills from the northern Lesotho - northeastern Free State region and demonstrates that on the basis of geochemistry, all 97 intrusions can be correlated with various units of the northern Barkly East and Lesotho Formations. In addition, the petrographical; characteristics, orientation and distribution of the dykes do not correlate with geochemistry. Geochemical discrimination diagrams have been used to identify five compositionally diverse dykes, which are similar to the northern Barkly East Formation units. Three dykes are characteristic of the Letele unit and two are compositionally similar to the Wonderkop unit. Although the geochemical characteristics of the Lesotho Formation units are rather well constrained, the composition of these units is typified by considerable overlap in composition. Therefore, since unambiguous classification of dykes with geochemical similarities to the various units of the Lesotho Formation is unachievable using an empirical approach, the multivariate forward-stepwise discriminant function analysis (DFA) technique was used to facilitate the classification of the remaining 89 dykes and three sills. Forward-stepwise DFA classified 23 dykes as having compositional similarities to the Mafika Lisiu unit, 29 as having compositions of the Maloti or Senqu types; and 32 as having the composition of the Mothae type. In addition, eight dykes are compositionally similar to the Oxbow dykes, which intrude the Senqu unit in northern Lesotho. These results suggest that that the Lesotho remnant was fed from local eruption sites and that long distance magma transport for the bulk of the Lesotho remnant basalt lavas is unlikely.
Keywords: Flood basalts -- Lesotho; Volcanism -- Lesotho; Magmatism -- Lesotho; Dikes (Geology) -- Lesotho; Geochemistry -- Lesotho; Lava -- Lesotho